Penyuluhan Mengenal Digital Finance dan Aplikasi Keuangan di Desa Bunga Tanjung Kabupaten Kerinci - Bustami, Alek Wissalam; Mahabbati, Suci; Syukrawati, Syukrawati; Tiara, Tiara; Wahyuni, Endah Sri; Nilda, Elvi; Bustami, Bustami; Putra, Eka (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Hiang Village, Setinjau Laut District, face challenges of limited visibility and market access due to the minimal utilization of digital technology. This low technology adoption is caused by a lack of knowledge, skills, and awareness regarding the potential of digital marketing. This community service activity aimed to enhance the capacity of MSME owners in utilizing Google Maps as a tool to increase their business visibility. The method employed was a participatory counseling approach, which included three stages: planning, implementation (consisting of socialization, theoretical presentation, and hands-on practice), and evaluation (through a post-test, feedback, and monitoring). The results showed a significant increase in participants' understanding, with over 90% passing the post-test. Moreover, there was a high rate of technology adoption, with 84% of participants successfully registering their businesses on Google Maps after the training. It is concluded that this outreach activity was effective in empowering MSMEs, providing a practical solution to the visibility problem, and serving as a strategic first step in bridging the digital divide in rural areas.